The Effect of Transparency on Brand Loyalty - Yuana, Irkhamnah Aisyah; Sutarso, Yudi (IPTEK Journal of Proceedings Series, 2020)
Bank needs to provide best services to minimize customer’s complaint. One of bank efforts to serve their customers can be done by using transparency, so that all information is conveyed clearly. Transparency is also expected to enhance brand loyalty of customers. This conceptual study is based on theoretical review from literatures and previous researches related with these concepts. The basic concept of theory used in this study is that customers who get operational transparency express greater trust and support. This study aimed to analyze the effect of transparency on brand loyalty. By classifying the result of previous researches, this study found some propositions : (1) transparency has a significant effect on brand trust of customer; (2) brand trust has a significant effect on brand satisfaction of customer (3) brand trust has a significant effect on brand loyalty